COMPLETE ANDROGEN INSENSITIVITY SYNDROME WITH MALIGNANT LEFT TESTICULAR SEMINOMA- A CASE REPORT - Maria, AB Dorothy; Wong, PS; Hafiz, P Muhammad; Tong, CV; Rosli, I (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Complete androgen insensitivity syndrome (CAIS) is a rare X-linked recessive disorder resulting in failure of normal masculinization of the external genitalia in chromosomally male individuals. We present a rare case of CAIS with malignant left testicular seminoma. RESULTS A 37-year-old phenotypically female patient presented with primary amenorrhea at 15 years old and was diagnosed with CAIS based on chromosomal studieswhich revealed 46XY. However, she defaulted follow-up until she presented again with abdominal distension and breathlessness in April 2020. She is the 3rd of 4 siblings from a non-consanguineous marriage. Physical examination revealed a tall, normal built girl with no axillary and pubic hair, Tanner Stage 1 breast and normal female genitalia. CT of the thorax, abdomen and elvis revealed a large heterogeneous suprapubic mass (10.6 cm x 13.5 cm x 17.2 cm), moderate ascites, enlarged left paraaortic lymph node, massive right pleural effusion and a rudimentary uterus. Laparotomy and bilateral orchidectomy was performed which revealed left testicular seminoma and normal right testis on histopathologic examination. Tumor markers post-operatively revealed elevated serum LDH lactate dehydrogenase, and normal serum alpha feto protein and serum beta human chorionic gonadotrophin. She underwent 4 cycles of bleomycin, etoposide and platinum chemotherapy. Post-chemotherapy CT revealed no recurrence or distant metastasis with normalization of her tumour markers. Serum follicle-stimulating and serum luteinizing hormones were elevated; serum testosterone level was within normal. 25-hydroxyvitamin D level was insufficient. Dual energy x-ray absorptiometry scan revealed low bone mineral density. She was started on cholecalciferol 1000 IU daily and premarin 0.625 mg daily. CONCLUSION This case highlights the importance of proper follow up and management of CAIS to prevent complications, such as malignant germ cell tumor and osteoporosis.